Pelayanan Administrasi Akademik di Lingkungan Program Pascasarjana Universitas Riau - Syafril Safril; Zaili Rusli; Febri Yuliani (Jurnal EL-RIYASAH, 2022)
Universities as institutions that provide higher education have the responsibility to prepare most of their graduates to become qualified, professional and competent graduates. Riau University as a higher education institution within the Ministry of National Education which organizes academic and/or professional education programs in the field of science, including: creation, application, and development of science, technology, and/or arts. The Postgraduate Program of the University of Riau is required to be able to create an academic atmosphere that is more conducive to scientific activities, and to create a management and service system whose quality is increasing as well as developing an improving teaching and learning process. Indicators in order to assess the success of achieving the mission of developing the Postgraduate Program comprehensively. This study aims to analyze Academic Administration Services in the Postgraduate Program at the University of Riau by using qualitative research methods (Qualitative Research) to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups.The results showed that administrative services in the Postgraduate Program at the University of Riau ranging from New Master Admissions, New Student Re-registration, Online KRS Filling, Lectures, Additions/cancellations of courses, Determination of supervisory commissions, Research Proposal Seminars, Research Results Seminars, and Examinations Thesis trial has been going well. The seriousness of the Postgraduate Program at the University of Riau in the implementation of services and other tasks has almost no significant obstacles, it's just that there are some shortcomings that need to be addressed such as facilities that support optimally, good communication with students. In addition, in terms of service, it can be seen from the responsiveness, responsibility, and accountability that it is classified as good.